The Government Policy of ’Free Visa, Free Ticket’: An Evaluation from Prospective Foreign Labour Migrant - Rai, Pushpa Raj (Patan Pragya, 2022)
Nepali youths join foreign jobs with the dream of earning a lot of money and making a happy family. However, high visa fees and high costs of tickets impose a load of debt on the family. Nepal adopted the policy of free visas and free tickets to reduce the burden of debt. This article explains whether the dream of foreign labor migrants has come true after the government of Nepal adopted the policy of the 'free visa, free ticket' policy. The main objective of this article is to describe the experience of foreign labour migrants under the policy of the 'free visa, free ticket'. Seven years have passed since the 'free visa, free ticket' policy was introduced. Foreign labour migrant’s have-not been able to go abroad for work at zero migration cost yet. Due to ineffectiveness of this policy, people who go abroad have become a place to cheat on.